MUS-2, a novel variant of the chromosome-encoded β-lactamase MUS-1, from Myroides odoratimimus. (September 2015) - Al-Bayssari, C.; Gupta, S. Kumar; Dabboussi, F.; Hamze, M.; Rolain, J.-M.
Abstract: The aim of the present study was to investigate the molecular mechanism of carbapenem resistance of three imipenem-resistant isolates of Myroides odoratimimus recovered from two livestock farms of cows and pigeons by rectal swab in Lebanon in January 2014. Investigation of imipenem resistance of these isolates using the modified Hodge test, the EDTA test, the modified CarbaNP test and the matrix-assisted laser desorption/ionization time-of-flight mass spectrometry Ultraflex assay showed a carbapenemase activity due to the presence of a chromosome-encoded β-lactamase MUS, verified by PCR. However amplification and sequencing of this chromosomal gene showed a novel variant of it designated MUS-2 by the curators of the Lahey database of β-lactamases (http://www.lahey.org/Studies/webt.asp ). Cloning of the bla MUS-2 was performed, followed by protein expression in Escherichia coli TOP 10. Pulsed-field gel electrophoresis clearly showed that the three isolates belonged to the same clone. This study reports a novel variant of the chromosome-encoded bla MUS-1 associated with carbapenem resistance in Myroides odoratimimus and shows that animals may represent a reservoir of bacteria harbouring several variants of resistance genes.